2020
DOI: 10.1111/liv.14554
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hepatic and systemic angiopoietin‐like 3, hepatic Vitamin D receptor expression and NAFLD in obesity

Abstract: Background & Aims Non‐alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide and an independent risk factor for cardiovascular mortality. Angiopoietin‐like proteins (ANGPTLs) are targets for vitamin D receptor (VDR)‐mediated gene transcription and this axis may promote NAFLD. ANGPTL3 is a hepatokine which inhibits lipoprotein lipase and its experimentally induced inactivation reduces hepatosteatosis. Little is known on ANGPTL3 in human NAFLD and no data exist on its relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 55 publications
0
21
0
1
Order By: Relevance
“…Several studies have observed elevated ANGPTL protein levels in NAFLD patients. Plasma ANGPTL3 levels are higher in biopsy-proven NASH patients [ 92 , 93 ], and plasma [ 94 , 95 ] and hepatic [ 96 ] ANGPTL8 are elevated in patients with fatty liver independent of insulin resistance [ 94 ]. In addition to inhibiting LPL activity, ANGPTL8 seems to favors TG accumulation in hepatocytes.…”
Section: Dyslipidemia: Linking Hepatic Lipid Metabolism and The Heartmentioning
confidence: 99%
“…Several studies have observed elevated ANGPTL protein levels in NAFLD patients. Plasma ANGPTL3 levels are higher in biopsy-proven NASH patients [ 92 , 93 ], and plasma [ 94 , 95 ] and hepatic [ 96 ] ANGPTL8 are elevated in patients with fatty liver independent of insulin resistance [ 94 ]. In addition to inhibiting LPL activity, ANGPTL8 seems to favors TG accumulation in hepatocytes.…”
Section: Dyslipidemia: Linking Hepatic Lipid Metabolism and The Heartmentioning
confidence: 99%
“…Angiopoietin-like protein 3 (ANGPTL3) is secreted mainly by the liver and, in this sense, it might be considered a hepatokine. ANGPTL3 acts as dual inhibitor of lipoprotein lipase and endothelial lipase, thereby increasing plasma NEFA, triacylglycerols, LDL-cholesterol and HDL-cholesterol, and its plasma concentration is associated with clinical/ histological markers of NAFLD/NASH and with hepatic ANGPTL3 expression [122]. Evinacumab is an [123,124].…”
Section: Drugs Targeting Hepatokinesmentioning
confidence: 99%
“…The diagnosis of NAFLD/NASH was performed on liver biopsies based on validated criteria [65,66]. Experimental procedures for liver fragments examination are detailed in our previous study [67]. Two pathologists blinded to patients' identity performed all the histological analyses.…”
Section: Histological and Gene Expression Analysesmentioning
confidence: 99%